The Effect of Conversation Topic and Level of Formality on Stance in Spoken American English : A Corpus-Based Study - Islam Hamdy Mohammed Abdelma{u2019}boud; Amira Agameya; Eenas Metwaly (Cairo : Islam Hamdy Mohammed Abdelma{u2019}boud, 2022)
This study contributed to previous research on stance as it examined the influence of formality level and conversation topic on the use of epistemic and attitudinal stance. The research depended on quantitative as well as qualitative linguistic analysis of data from the Corpus of Contemporary American English (COCA), a ready-made corpus, as well as The Religious Debate Corpus (RDC), and the Political Debate Corpus (PDC); two corpora compiled by the researcher. The frequencies of occurrence of hedges, boosters, and attitude markers were identified in the Spoken sub-corpus, one of the spoken sub-corpora of COCA representing a higher level of formality, to be compared to the TV/Movies sub-corpus, which represents a lower level of formality, in order to investigate the influence of formality level on the use of stance expressions. Likewise, the frequencies of the three stance categories were compared in two corpora of different conversation topics: the RDC, and the PDC with the purpose of exploring the influence of conversation topic on the use of stance expressions. Overall, the results yielded showed an influence of formality level on all stance categories, and an impact of conversation topic on all stance categories with the exception of boosters. These findings are attributed to the nature of the corpora investigated
Thesis (Ph.D.) - Cairo University - Faculty of Arts - Department of English Language and Literature
Issued also as CD
Keywords: hedges; boosters; Stance; stance-taking